Penerapan Media Poster Angka untuk Meningkatkan Hasil Belajar Siswa Matematika Kelas 1 Sekolah Dasar - Anandita Fajriyah; Binti Khoiriyah; Pixioriza (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Application of Number Posters to Improve Student Learning Outcomes in Grade 1 Mathematics at the UPTD of SD Negeri 1 Hargomulyo. Thesis, Faculty of Teacher Training and Education, Nahdlatul Ulama University, Lampung, January 2026. Mathematics learning in grade 1 at the UPTD of SD Negeri 1 Hargomulyo still shows low learning outcomes due to the teacher-centered learning process, which makes students experience difficulties in understanding the material. Therefore, the application of creative and appropriate learning media is needed, one of which is through the use of number posters. This study aims to improve student learning outcomes in mathematics through the application of number posters in grade 1 at the UPTD of SD Negeri 1 Hargomulyo. This study used the Classroom Action Research (CAR) method, implemented in two cycles. Each cycle consisted of planning, implementation, observation, and reflection. The subjects of this study were 20 grade 1 students at the UPTD of SD Negeri 1 Hargomulyo. Data collection techniques included observation, interviews, documentation, and learning outcome tests. Data analysis used a mixed methods approach. The results showed that the implementation of number posters improved the mathematics learning outcomes of first-grade students at the UPTD SD Negeri 1 Hargomulyo. Initial data obtained from daily test scores showed that 50% of students completed the course, with completion increasing to 55% in the first cycle. In the second cycle, this increased significantly to 85%. Based on these findings, it can be concluded that the implementation of number posters improved the mathematics learning outcomes of first-grade students at the UPTD SD Negeri 1 Hargomulyo.